Development of RESTORE: an online intervention to improve mental health symptoms associated with COVID-19-related traumatic and extreme stressors. Issue 1 (1st January 2021) - Trottier, Kathryn; Monson, Candice M.; Kaysen, Debra; Wagner, Anne C.; Pun, Carson; Abbey, Susan E.
ABSTRACT: Background: Frontline healthcare workers, recovered COVID+ patients who had severe illness, and close others of COVID+ patients who have recovered or died are at risk for clinical levels of mental health symptoms in the context of the COVID-19 pandemic. RESTORE (R ecovering from E xtreme S tressors T hrough O nline R esources and E -health) was specifically designed for this context. RESTORE is a transdiagnostic guided online intervention adapted from evidence-based cognitive-behavioural therapies. Objectives: RESTORE was designed to address depression, anxiety, and posttraumatic stress disorder symptoms associated with exposure to COVID-19-related traumatic and extreme stressors, and to overcome multiple barriers to accessing psychotherapies. Method: This paper describes the intervention components and platform, as well as the principles used to develop RESTORE. Current research and future directions in developing and testing RESTORE are outlined. Results: Preliminary data from an initial uncontrolled trial evaluating RESTORE in frontline healthcare workers is highly promising. Conclusion: We believe RESTORE has great potential to provide accessible, evidence-based psychological intervention to those in great need. HIGHLIGHTS: RESTORE is a transdiagnostic online intervention adapted from evidence-based cognitive-behavioural therapies designed to address mental health symptoms related to exposure to COVID-19-related traumatic and extreme stressors, and to overcome barriers to accessing psychotherapy.